Exotic Citrus Diseases: Early Detection is the Solution to Protecting Florida Citrus - Ron H. Brlansky; Megan M. Dewdney; Jamie D. Yates (EDIS)
This revised illustrated trifold brochure provides key information about Pseudocercospora fruit and leaf spot, sweet orange scab, citrus leprosis virus, citrus variegated chlorosis (CVC), and citrus tristeza virus (CTV) stem pitting. Includes contact information for UF/IFAS Extension citrus experts. Written by R. H. Brlansky, M. M. Dewdney, and J. D. Yates and published by the UF Department of Plant Pathology, June 2010.